Survey of prenatal testing for genetic disorders in Japan: Recent report. Issue 4 (18th February 2016) - Nobuzane, Takahiro; Yamada, Takahiro; Miura, Kiyonori; Sawai, Hideaki; Masuzaki, Hideaki; Kudo, Yoshiki
Abstract: Aim: In order to investigate the current status of prenatal testing for genetic disorders, we conducted a multicenter retrospective questionnaire survey. Methods: The questionnaire was sent to 105 facilities with genetic counseling systems. The questionnaire consisted of two parts: (i) the number of prenatal tests conducted for genetic disorders from January 2010 to December 2012, whether the laboratory was combined with the counseling facility or separate, the sampling procedure method, the testing results, and the outcomes of the affected fetus in addition to treatment; and (ii) a survey of personal comments regarding prenatal testing for genetic disorders. Results: We received responses from 69 of the 105 facilities (65.7%), and genetic testing was performed at 26 of these facilities. Nucleic acid sequential testing was performed on 45 disorders and 252 cases during a three‐year period. There were 67 cases of affected fetuses. Six cases continued pregnancy and were treated. The comment survey highlighted difficulties in locating a laboratory to assess prenatal samples, as well as inadequate counseling and preparation for genetic disorders. Conclusions: Our study revealed that a number of prenatal testing for genetic disorders are conducted in Japan; however, it is difficult for counselors to locate a laboratory capable of testing for specific genetic disorders. Inadequate counseling and healthcare providers' lack of knowledge is a current problem. A well‐established system of prenatal testing for genetic disorders and the further education of general physicians is required.